Enhancing Service Delivery of the Provincial Waterworks Authority, Ban Bueng Branch via LINE Chatbot and Customer Care OA in the Digital Age - สุขกรี เมษาวดี; นักเคน ธนพร; สุทธยานานนทชัย สุจารี; เจียรโณรส พลอยไพลิน; ศรีสุพจนานนท์ สุนิพันธ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aims to develop a LINE-based Chatbot system to improve the service delivery of the Provincial Waterworks Authority, Ban Bueng Branch. The objectives are: (1) to design and implement an automated Chatbot for providing information and answering inquiries about waterworks services via the LINE application; (2) To improve the efficiency of service delivery by enhancing convenience and speed, and to develop a promotional video demonstrating the procedures for online water bill payments and digital communication with the authority; and (3) to evaluate the system’s performance in meeting users’ needs. The scope of development included both the Chatbot system and a promotional video to support user engagement. The system was tested with two groups of users: 20 staff members and 273 members of the public. Staff feedback indicated a high level of overall satisfaction (mean = 4.31, SD = 0.76), with the highest rating for information coverage and service accessibility via the Chatbot (mean = 4.46, SD = 0.67). Public users reported a very high level of satisfaction (mean = 4.54, SD = 0.43), particularly in overall user experience (mean = 4.62, SD = 0.36), followed by ease of use, accuracy of information, system responsiveness, and information coverage. The results demonstrate that the Chatbot system and accompanying promotional media effectively enhance the efficiency of online services. The system provides timely and accurate information, improves user convenience, and reduces staff workload while addressing users’ needs in a comprehensive and efficient manner.